2021
DOI: 10.52098/airdj.202144
|View full text |Cite
|
Sign up to set email alerts
|

Using Augmented Reality and Drones in Tandem to Serve Smart Cities

Abstract: Augmented Reality Technologies as such have been known since the first decade of the 21st century. However, due to the relatively high costs of terminal equipment, the lack of mass demand in industries, their unpreparedness to implement augmented reality in production processes, the limited use of augmented reality in the educational process, etc., this technology did not become networked. In the broadest sense of this word, the traffic generated by augmented reality significantly affects both the principles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The different types of UAVs employed in various FANET scenarios can be classified based on such different factors as UAV size, weight, range, endurance, altitude, application, flying mechanism, ownership, airspace class, level of control (autonomy), and type of engine [4]. Recently, several studies have shown the importance of FANETs by investigating the integration of FANETs of UAVs with different technologies, including Virtual Reality (VR), [5][6][7][8][9], IoT [10][11][12], flying edge computing [13], flying fog computing [10,14,15], cellular networks [16][17][18][19], and flying cloud computing [20]. Although such integration brings many advantages, many issues may arise as well, ranging from UAV deployment issues to regulations on using these devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different types of UAVs employed in various FANET scenarios can be classified based on such different factors as UAV size, weight, range, endurance, altitude, application, flying mechanism, ownership, airspace class, level of control (autonomy), and type of engine [4]. Recently, several studies have shown the importance of FANETs by investigating the integration of FANETs of UAVs with different technologies, including Virtual Reality (VR), [5][6][7][8][9], IoT [10][11][12], flying edge computing [13], flying fog computing [10,14,15], cellular networks [16][17][18][19], and flying cloud computing [20]. Although such integration brings many advantages, many issues may arise as well, ranging from UAV deployment issues to regulations on using these devices.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, UAVs that can freely fly in the sky are excellent tools for collecting 3D data. Several studies have investigated the use of VR technology and UAV networks [5][6][7][8][9]. The main challenges of UAV-enabled VR include the low battery lifetime and computing capacity of VR users, which in turn cause issues with content caching and transmission.…”
mentioning
confidence: 99%